The origins of intensive marine fishing in medieval Europe: the English evidence - Locker, A M; Roberts, C M; Barrett, J H (Proceedings of the Royal Society of London. Series B: Biological Sciences, 2004)
The catastrophic impact of fishing pressure on species such as cod and herring is well documented. However, the antiquity of their intensive exploitation has not been established. Systematic catch statistics are only available for ca. 100 years, but large-scale fishing industries existed in medieval Europe and the expansion of cod fishing from the fourteenth century (first in Iceland, then in Newfoundland) played an important role in the European colonization of the Northwest Atlantic. History has demonstrated the scale of these late medieval and post-medieval fisheries, but only archaeology can illuminate earlier practices. Zooarchaeological evidence shows that the clearest changes in marine fishing in England between AD 600 and 1600 occurred rapidly around AD 1000 and involved large increases in catches of herring and cod. Surprisingly, this revolution predated the documented post-medieval expansion of England's sea fisheries and coincided with the Medieval Warm Period-when natural herring and cod productivity was probably low in the North Sea. This counterintuitive discovery can be explained by the concurrent rise of urbanism and human impacts on freshwater ecosystems. The search for 'pristine' baselines regarding marine ecosystems will thus need to employ medieval palaeoecological proxies in addition to recent fisheries data and early modern historical records.